Reduced incidence of type 2 diabetes in patients with chronic hepatitis C virus infection cleared by direct‐acting antiviral therapy: A prospective study. Issue 12 (6th September 2020) - Adinolfi, Luigi E.; Petta, Salvatore; Fracanzani, Anna L.; Nevola, Riccardo; Coppola, Carmine; Narciso, Vincenzo; Rinaldi, Luca; Calvaruso, Vincenza; Pafundi, Pia Clara; Lombardi, Rosa; Staiano, Laura; Di Marco, Vito; et al.
Abstract: Aim: To assess the effect of hepatitis C virus (HCV) eradication on type 2 diabetes mellitus (T2DM). incidence. Methods: A prospective multicentre case–control study was performed, which included 2426 patients with HCV, 42% of whom had liver fibrosis stage F0‐F2 and 58% of whom had liver fibrosis stage F3‐F4. The study population consisted of a control group including 1099 untreated patients and 1327 cases treated with direct‐acting antivirals (DAAs). T2DM incidence was assessed during a median (interquartile range) follow‐up period of 30 (28–42) months. Risk factors for T2DM were assessed using a Cox regression model (relative risk [RR], hazard ratio [HR], Kaplan–Meier analysis). Insulin sensitivity was evaluated by homeostatic model assessment (HOMA) and changes by repeated‐measures ANOVA. Factors independently associated with T2DM were assessed by multivariate analysis. Results: The absolute incidence of T2DM for controls and cases was 28 and 7/1000 person‐years, respectively ( P = 0.001). In cases compared to controls, HCV clearance reduced the RR and HR of T2DM by 81% and 75% to 93%, respectively ( P = 0.001). It was calculated that, for every 15 patients who obtained HCV clearance, one case of T2DM was saved. HCV clearance was associated with significant reductions in HOMA‐insulin resistance and HOMA‐β‐cell function and an increase in HOMA‐insulin sensitivity, as assessed in 384 patients before and after HCV clearance. At multivariate analysis, HCV clearance emerged as independently associated with a reduced T2DM risk. Conclusion: The results showed that HCV clearance by DAA treatment reduces T2DM incidence probably by restoring the HCV‐induced alteration of glucose homeostasis mechanisms.